Reliability of the OMERACT Giant cell arteritis Ultrasonography Score (OGUS): results of a patient-based exercise involving experts and non-experts in vascular ultrasonography - Christian Dejaco; Stavros Chrysidis; Sara Monti; Cristina Ponte; Peter Mandl; Lene Terslev; Bhaskar Dasgupta; Alojzija Hočevar; Christina Duftner; Wolfgang Schmidt; Carlos Pineda; Eugenio De Miguel; et al. (RMD Open)
Objective To test the reliability of the Outcome Measures in Rheumatology Giant cell arteritis (GCA) Ultrasonography Score (OGUS) and other composite scores in a patient-based exercise involving experts and non-experts in vascular ultrasonography.Methods Six GCA patients were scanned twice (two rounds separated ≥3 hours) by 12 experts and 12 non-experts. Non-experts received 90 min of theoretical and 240 min of practical training between rounds 1 and 2. Ultrasonography was conducted on temporal arteries (common superficial, frontal and parietal branches) and axillary arteries bilaterally to calculate the OGUS, the Southend score and the Halo count. Inter-reader and intra-reader reliability were assessed by intraclass correlation coefficient (ICC).Results Mean age of GCA patients was 78±5.1 years, 2 (33.3%) were women, and all were in clinical remission. Expert inter-reader ICC of the OGUS was 0.60 in both rounds, 0.40 in round 1 and 0.51 in round 2 for the Southend score and 0.45 and 0.52, respectively, for the Halo count. Median ICCs for intra-reader reliability were 0.86, 0.73 and 0.65 for the OGUS, Southend score and Halo count, respectively.For non-experts, inter-reader ICCs in round 1 were 0.20 for the OGUS, 0.20 for a normalised Southend score (=score divided by available segments) and 0.35 for a normalised Halo count. After training, inter-reader reliability ICCs improved to 0.52, 0.29 and 0.54, respectively.Conclusion Inter-reader reliability was fair to moderate, and intra-reader reliability was good for OGUS, Southend score and Halo count among experts. Inter-reader reliability of non-experts in vascular ultrasonography improved after the training.